THE SOLUTION OF MATHEMATICAL MODEL OF OTOBUS TICKET SALES WITH REFERRAL MARKETING STRATEGY - Putra, Dewa Putu Wiadnyana; Ruditho, Marcellinus Andy (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
One of the ways to involve customers in marketing strategies is known as the referral strategy. This strategy has been applied in various fields for marketing, one of which is in the field of transportation. This study aims to determine the solution to the mathematical model of bus ticket sales using a referral strategy. The data in this study is bus passenger data throughout 2020 which was obtained from one of the Otobus companies in Jakarta. Mathematical model that is compiled using the analogy of the model of the spread of disease. The results of this study are a mathematical model of bus ticket sales using a referral strategy consisting of 4 compartments. The model solution is determined by iterating over the system of differential equations that has been formed. Based on the solution obtained, the simulation results show that the referral strategy in bus ticket sales is able to increase bus passengers up to 39.92%.